Need Assesment of Guidance and Counseling Module to Improve Freshmen Self-Adjustment - Rizky Andana Pohan; Mawardi Siregar (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2020)
Adjustment has become one of the global problems for freshmen in the world. Intervention in the form of psychoeducation is needed to accelerate and increase the adaptive capacity of freshmen in tertiary institutions. The module is an alternative assistance that can be used by the counselor to help him. This study aims to analyze the description of the needs for guidance and counseling modules to improve the adjustment of freshmen. The research method used is a quantitative approach through a random survey of 112 students of the Islamic Guidance and Counseling Study Program of the Langsa State Islamic Institute through the Google Forms application in June 2020. The literature study rests on module theory and adjustment, while the analysis of the survey results analyzed through descriptive statistical analysis techniques by looking at the categorization of student answers. The results showed that freshmen had problems in their adjustment process. The freshmen need for guidance and counseling modules to assist him in the adjustment process is in a high category. Therefore, guidance and counseling modules to improve self-adjustment according to the characteristics of freshmen and their environment need to be developed immediately.